Mobile-Based Academic Course Registration System in College of Art and Sciences of Universiti Utara Malaysia - Makhmudjon, Karimov (2009)
Currently academic course registration is available through the Computer Center counter as well as online computer. However, through the counter, this service is only available during office hours. Even though through online computer, users are able to access the services anytime, but they must be connected to the Internet which limits their access to this service. Since the need of course registration increases rapidly during course registration period, an alternative technology is required. Thus, mobile technology has been identified as a potential alternative since it is able to provide the course registration service anytime and anywhere. This paper discusses a prototype of Mobile-based academic course registration system (MBACRS), a facility which has been developed for students to register their academic courses through mobile devices. MBACRS was developed as an alternative channel for registering academic courses through mobile devices.Results of user evaluation on the MBACRS indicate that it has good usability in terms of Usefulness, Ease of Use and Outcome/Future Use. The results also indicate that it is useful for users and it is capable to help them to make their academic course registration easily, directly and successfully regardless of location and time.